Pelatihan Penulisan Artikel Ilmiah (Jurnal) dalam Rangka Pengembangan Keprofesionalan Berkelanjutan Guru-Guru IPA di Kabupaten Bengkulu Tengah - Desy Hanisa Putri; Dedy Hamdani; Dini Syafitri; Defianti, Aprina (Universitas Nusantara PGRI Kediri, 2022)
The Continuing Professional Development Program (CPD) aims to develop teacher professionalism. CPD is carried out in accordance with the needs of teachers to achieve professional competency standards and/or increase their competence above their professional competency standards which at the same time has implications for the acquisition of credit points for promotions/functional positions of teachers. One of the things that is part of the PKB is scientific publications. Currently, teachers are still having difficulty writing scientific research articles that meet the requirements of scientific publication in a scientific journal. The results of a survey of science teachers in Bengkulu Tengah Regency, only 18.75% of teachers have ever submitted scientific articles to a scientific journal. Based on these results, a service was carried out which aimed to (1) increase the knowledge of science teachers in Central Bengkulu Regency about writing scientific articles in journals and (2) increase the motivation of science teachers in Central Bengkulu Regency to write scientific articles in journals.